Photoinduced triplet-state electron transfer of platinum porphyrin: a one-step direct method for sensing iodide with an unprecedented detection limit. Issue 13 (18th February 2015) - Masih, Dilshad; Aly, Shawkat M.; Alarousu, Erkki; Mohammed, Omar F.
Abstract : Herein, we report for the first time the photoinduced triplet-state electron transfer of Pt(ii )TMPyP as an easy, rapid, environmentally friendly, ultra-sensitive and economical method for the determination of iodide in the aqueous phase. Abstract : Here, we report for the first time a one-step direct method for sensing halides in aqueous solution using phosphorescence quenching of platinum-cationic porphyrin. This method offers an easy, rapid, environmentally friendly, ultra-sensitive (with a previously unattained detection limit of 1 × 10 −12 M) and economical method for the determination of iodide. To fully understand the reaction mechanism responsible for the phosphorescence quenching process, we have employed cutting-edge time-resolved laser spectroscopy with broadband capabilities.